2012
DOI: 10.1016/j.foodpol.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Common Agricultural Policy effects on dynamic labour use in agriculture

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
3
39
1
8
Order By: Relevance
“…Policy makers should provide some guidance regarding planting and cropland management and introduce the surplus rural labor to work in cities. Petrick and Zier (2012) confirmed that common agricultural policy could adjust reasonable labor use in agriculture and raise general wage levels. With simulation of the rate of decreasing onion production and rate of increasing migrant workers on Minqin basis, the net household profit could be increased if low prices of agricultural products could be predicted.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 81%
“…Policy makers should provide some guidance regarding planting and cropland management and introduce the surplus rural labor to work in cities. Petrick and Zier (2012) confirmed that common agricultural policy could adjust reasonable labor use in agriculture and raise general wage levels. With simulation of the rate of decreasing onion production and rate of increasing migrant workers on Minqin basis, the net household profit could be increased if low prices of agricultural products could be predicted.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 81%
“…() find that a subsidy promoting ‘development and structural adjustment of rural areas’ affects agricultural employment in France negatively. By analysing the dynamic labour use, Petrick and Zier () find that investment aids slow down job reductions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Petrick and Zier (2011) find that the farm investment aids and transfers to less developed areas have no impact on employment, and Schmitt et al (2004) find that a subsidy promoting 'development and structural adjustment of rural areas' affects agricultural employment in France negatively. By analysing the dynamic labour use, Petrick and Zier (2012) find that investment aids slow down job reductions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Petrick and Zier (2012), who studied the effect of the CAP direct payments and the rural development measures on unemployment in agriculture, determined that the CAP has a very limited impact on either the agricultural job creation or maintenance. Although, Ahearn et al (2006) or Bartolini and Viaggi (2013) have emphasized the CAP's substantial effect -particularly in relation to its direct payments -on changes in the agricultural structure.…”
mentioning
confidence: 99%